Decapitation and paramilitary feuds in Northern Ireland, 1969-1992. Issue 4 (2nd October 2022) - Sanders, Andrew
ABSTRACT: This article seeks to draw together two major themes in studies of political violence, namely, decapitation and factionalism, using examples from the Irish republican paramilitary groups that emerged during the period of conflict in Northern Ireland commonly known as the Troubles. I seek to complement the extensive literature across these areas by offering analysis of the behaviour of Irish republican paramilitary groups during internecine feuds that took place between the 1969 split in the Irish Republican Army and the 1992 Provisional Irish Republican Army action against the Irish People's Liberation Organisation. By comparing three inter-group feuds, this study will demonstrate the prevalence of decapitation attacks in the aftermath of factional splits and the serious consequences that they have for groups which suffer a decapitation attack.